2004
DOI: 10.1002/bin.150
|View full text |Cite
|
Sign up to set email alerts
|

Determining the influence of tangible items on screaming and handmouthing following an inconclusive functional analysis

Abstract: A brief experimental analysis was used to compare the effects of the presence of tangible objects in an alone condition following an inconclusive functional analysis of screaming and handmouthing behavior of an 8-year-old boy. The alone condition with tangibles involved having toys available throughout the session with no interaction from the therapist and produced a higher percentage of intervals with screaming and handmouthing. The study demonstrates the importance of evaluating the effects of the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…Interestingly, each participant displayed high levels of what was arguably a more salient form of stereotypy during TV (with visual and audio) than during No TV (low ambient stimulation). This finding is consistent with previous studies (Carter et al, 2004;Rapp, 2004;Van Camp et al, 2000) and is potentially important because it suggests that merely enriching the environment with preferred stimulation may produce undesirable effects on automatically reinforced behavior. Specifically, the The highest probability stereotypy prior to the TO body rock phase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, each participant displayed high levels of what was arguably a more salient form of stereotypy during TV (with visual and audio) than during No TV (low ambient stimulation). This finding is consistent with previous studies (Carter et al, 2004;Rapp, 2004;Van Camp et al, 2000) and is potentially important because it suggests that merely enriching the environment with preferred stimulation may produce undesirable effects on automatically reinforced behavior. Specifically, the The highest probability stereotypy prior to the TO body rock phase.…”
Section: Discussionsupporting
confidence: 93%
“…Although a recent review by Rapp and Vollmer (in press) concluded that most forms of stereotypy are automatically reinforced, little is known about specific antecedent events that may influence automatically reinforced behavior. In fact, the antecedent event that most often associated with stereotypy is 'low environmental stimulation' with and without reference to social and tangible reinforcers (e.g., Berkson & Davenport, 1962;Berkson & Mason, 1963, 1964Emerson, Hatton, Robertson, Henderson, & Cooper, 1999;Hall, Thorns, & Oliver, 2003;Horner, 1980;Iwata, Dorsey, Slifer, Bauman, & Richman, 1982/1994.A handful of studies have shown that the presence of a particular, often preferred, stimulus sets the occasion for some individuals to engage in automatically reinforced problem behavior (Carter, Devlin, Doggett, Harber, & Barr, 2004;Friman, 2000 Rapp, 2004;Van Camp et al, 2000). Friman demonstrated that a young child engaged in thumb sucking only when he held a small cloth.…”
mentioning
confidence: 97%
“…Of the 37 BFA studies included in this review, five studies, 13.5%, contained at least one BFA that produced either initially inconclusive or completely inconclusive results (Carter et al 2004;Derby et al 1992;Perrin et al 2008;Rapp et al 1999;Vollmer et al 1995). All other BFAs successfully identified behavioral function.…”
Section: Outcomes Of Brief Functional Analysismentioning
confidence: 91%
“…All other BFAs successfully identified behavioral function. Seven studies, 18.9%, did not include any form of treatment evaluation (Carter et al 2004;Kahng and Iwata 1999;LaBelle and Charlop-Christy 2002;Normand et al 2008;Oikawa et al 2011;Reimers et al 1993;Vollmer et al 1995). Of the studies that did incorporate a treatment, 96.7% reported that the treatment led to decreases in problem behavior, 50% reported treatment led to increases in appropriate behavior, 13.3% reported some evidence of generalization of treatment effects, and 10% demonstrated maintenance of treatment effects over a period of time.…”
Section: Outcomes Of Brief Functional Analysismentioning
confidence: 93%
See 1 more Smart Citation